Position and Commercial Dynamism of Exports in the Fishing Sector in Peru - Montes Ninaquispe, Jose Carlos; Castillo-Coronado, Yazmin; Chavesta Paico, Sheyla Johana; Chombo Jaco, José Alberto; Chavesta Paico, Eileen Lisset; Escalona Aguilar, Erik Omar; Ludeña Jugo, Diego Alejandro (LACCEI, 2024)
This research aims to analyze the position and commercial dynamics of Peru’s fisheries sector exports during the period 2014-2023. The methodology employed was quantitative, based on the analysis of statistical data from official sources, focusing on key indicators such as the number of importing countries, tariff headings, exporting companies, weight, and FOB value of exports. The results revealed significant fluctuations in these indicators, highlighting both opportunities and challenges in the diversification and expansion of the Peruvian fisheries market. Despite the instability, there are periods of notable growth that demonstrate the sector’s capacity for recovery and adaptation. Strategies are recommended to expand markets, diversify products, improve logistical infrastructure, and promote sustainable practices. Additionally, companies are advised to invest in innovation, develop internationalization strategies, and optimize operational efficiency. Financial and research institutions should provide technical and financial support.